2020
DOI: 10.1111/jonm.13009
|View full text |Cite
|
Sign up to set email alerts
|

A study on the relationship between nurses’ compulsory citizenship behaviours and job stress

Abstract: Aim To determine whether there is a relationship between compulsory citizenship behaviours and job stress among nurses working at public hospitals. Background Nurses may face strong pressure from their managers or peers to perform role behaviours beyond what is found in their job definition. When mandated, these extra duties are called compulsory citizenship behaviours. Method This descriptive study included 569 nurses who work in three hospitals. Data were analysed using descriptive statistical analyses, line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…The presented findings from the issue of coping with demanding situations with an emphasis on the coping with these situations in project manager work confirm the fact that this issue has long been paid attention, which corresponds to the amount of knowledge we have in this area, for example cited and described in , Gabrhelová (2020), Unaldi (2020) and Petru and Jarošová (2019) studies [1][2][3][4]. Despite a certain conceptual ambiguity, the inconsistency of the results of individual researches, various methodological approaches, the area of the research of coping with demanding situations in the different life contexts forms a relatively consistent area of knowledge.…”
supporting
confidence: 75%
“…The presented findings from the issue of coping with demanding situations with an emphasis on the coping with these situations in project manager work confirm the fact that this issue has long been paid attention, which corresponds to the amount of knowledge we have in this area, for example cited and described in , Gabrhelová (2020), Unaldi (2020) and Petru and Jarošová (2019) studies [1][2][3][4]. Despite a certain conceptual ambiguity, the inconsistency of the results of individual researches, various methodological approaches, the area of the research of coping with demanding situations in the different life contexts forms a relatively consistent area of knowledge.…”
supporting
confidence: 75%
“…Citizenship pressure is extremely harmful to employees’ work motivation ( De Clercq et al, 2019 ) and can seriously endanger their health and well-being ( Deery et al, 2017 ; He et al, 2019a ; Somech and Bogler, 2019 ) as it might be positively associated with job stress/burnout ( Zhang L. et al, 2018 ), work–family/work–leisure conflict and intention to quit ( Bolino and Turnley, 2005 ; Bolino et al, 2010 ; Youn et al, 2017 ; Banwo and Du, 2020 ). For instance, a significant relationship between nurses’ CCB and their experienced job stress was found by Ünaldi Baydin et al (2020) . In addition, Germeys et al (2019) argued that experiencing citizenship pressure will diminish employees’ autonomously/spontaneously motivated OCB while increasing their controlled OCB.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Although studies of OCBs are numerous in the literature (Yildiz, 2019), little is known about the disadvantages of these behaviours' dark side, compulsory citizenship behaviours (Vigoda‐Gadot, 2006). Past research has shown that compulsory citizenship behaviours are harmful to individuals and organizations (Ahmadian et al., 2017; He et al., 2018; Unaldi Baydin et al., 2020; Vigoda‐Gadot, 2006; Xia & Yadan, 2018). Despite the importance that this concept might have, especially for nurses as health care professionals, very few studies have focused on determining its antecedents and consequences (Harmanci Seren & Unaldi Baydın, 2017; Unaldi Baydin et al., 2020; Yildiz & Ayaz Arda, 2018; Yildiz & Yildiz, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Past research has shown that compulsory citizenship behaviours are harmful to individuals and organizations (Ahmadian et al., 2017; He et al., 2018; Unaldi Baydin et al., 2020; Vigoda‐Gadot, 2006; Xia & Yadan, 2018). Despite the importance that this concept might have, especially for nurses as health care professionals, very few studies have focused on determining its antecedents and consequences (Harmanci Seren & Unaldi Baydın, 2017; Unaldi Baydin et al., 2020; Yildiz & Ayaz Arda, 2018; Yildiz & Yildiz, 2016). This study's primary motivation is to fill this gap by investigating the consequences of compulsory citizenship behaviours, namely turnover intention and social loafing behaviours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation